Answer:
x = x - 4/6
false
Step-by-step explanation:
6(x - 1) - 4x = 2(3x - 5)
First, lets distribute the 6 to each item inside the parentheses on the left side. You can do this by multiplying the 6 by each term.
6 * x = 6x
6 * -1 = -6
6x - 6 - 4x = 2(3x - 5)
Next, we will combine like terms.
6x - 4x = 2x
2x - 6 = 2(3x - 5)
Now, let's look at the right side of the equation.
Let's distribute the 2 to each item inside the parentheses on the left side. You can do this by multiplying the 2 by each term.
2 * 3x = 6x
2 * -5 = -10
6x - 1 = 6x - 5
Immediately, we can tell this is false, but let's solve the equation just to make sure.
6x - 1 = 6x - 5
+1 +1
6x = 6x - 4
--- --------
6 6
x = x - 4/6
This is false.